Hubungan antara bimbingan orang tua dan motivasi belajar siswa dengan hasil belajar IPS siswa di sekolah dasar - Nur Pratama Jofi Saputra; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (Jurnal Pendidikan Dasar, 2021)
This study aims to 1) describe whether there is a relationship between parental guidance and social students learning outcomes of fifth-grade elementary school students; 2) describe whether there is a relationship between learning motivation and social students learning outcomes of fifth-grade elementary school students; 3) Describe whether there is a relationship between parental guidance and learning motivation together with the social students learning outcomes of fifth-grade elementary school students. This research uses a correlational study survey method. The population of this study was fifth-grade of state elementary school student in sub-district of Laweyan, Surakarta in the academic year 2020/2021. The sample was taken by using the Probability Sampling technique. Based on the data analysis, the research result w 1) there is a positive and significant relationship between parental guidance and social students learning outcomes of 32%; 2) there is a positive and significant relationship between learning motivation and social students learning outcomes of 26,2%; 3) there is a positive and significant relationship between parental guidance and learning motivation together with social student learning outcomes of 43.9%.